Cerebral phaeohyphomycosis: An important differential of tubercular brain abscess (Indian Journal of Case Reports, 2018)
Cerebral phaeohyphomycosis (CP), caused by dematiaceous fungi, is a serious form of central nervous system fungal infection. It is a rare disease with male predominance, no specific symptoms or signs and is associated with grim prognosis irrespective of the immune status of the patient. The disease is difficult to diagnose antemortem, and many cases are accidentally diagnosed during surgery or autopsy. The early diagnosis and appropriate treatment remain a challenge. The authors report a misinterpreted case of CP in a 53-year-old man without immunodeficiency who showed a favorable outcome after surgical excision and antifungal therapy. Therefore, CP should be an important differential in cases of brain abscess.